Environmental effects of pollution with heavy metals and bacterial pollutants in the rivers of the Amara district - Assistant Lect. Saad Farhan Banyan (Peerian Journals Publishing, 2023)
Drinking water has a vital role in human life, so it must be within international standards. Due to the many problems of pollution, this study was conducted to evaluate the water in the district of the city of Amara
Keywords: pollution; Amara River; sewage; heavy metals